Improving Teacher Quality Through Quality Professional Training and Inclusive Education (Inclusive Education: Welcoming Diversity in Schools) - Warti, Erlis; Arifannisa, Arifannisa (Global Education Journal, 2025)
This study aims to analyze the importance of improving teacher quality through high-quality professional training to support the implementation of inclusive education in schools. The focus of the study is directed at how systematically designed and sustainable training can improve teacher competency, both in pedagogical, professional, social, and personality aspects, so that they are able to deal with student diversity with a humanistic and adaptive approach. The method used is library research, by reviewing various literature sources such as books, scientific journals, previous research results, and relevant educational policies. Data were analyzed descriptively qualitatively to obtain a comprehensive picture of the relationship between teacher professional training and the implementation of inclusive education. The results show that high-quality professional training plays a significant role in developing teachers who are reflective, innovative, and have high social sensitivity to the needs of diverse students. Furthermore, inclusive education becomes a forum for actualizing teacher professionalism in creating a learning environment that is fair, participatory, and respectful of diversity. Thus, improving teacher quality and the implementation of inclusive education complement each other in realizing an excellent, humanistic, and socially just education system.